2021
DOI: 10.1186/s42234-021-00082-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Kinematic measures of the arm in chronic Stroke: part 2 – strong correlation with clinical outcome measures

Abstract: Background A detailed sensorimotor evaluation is essential in planning effective, individualized therapy post-stroke. Robotic kinematic assay may offer better accuracy and resolution to understand stroke recovery. Here we investigate the added value of distal wrist measurement to a proximal robotic kinematic assay to improve its correlation with clinical upper extremity measures in chronic stroke. Secondly, we compare linear and nonlinear regression models. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our findings are in agreement with the studies of Agrafiotis et al ( Agrafiotis et al, 2021 ) and Moretti et al ( Moretti et al, 2021 ), although they analyzed chronic stroke patients. Both studies found a significant correlation between RMK metrics and clinical outcomes (upper limb Fugl-Meyer Assessment ( Agrafiotis et al, 2021 ; Moretti et al, 2021 ), Motor Power ( Agrafiotis et al, 2021 ), NIH stroke scale ( Agrafiotis et al, 2021 ), modified Rankin scale ( Agrafiotis et al, 2021 ), Wolf Motor Function Test ( Moretti et al, 2021 ), Barthel Index ( Moretti et al, 2021 ), and Medical Research Council score ( Moretti et al, 2021 ) demonstrating that traditional stroke assessment scales can be accurately reproduced by robotic measurements. The outcomes of these studies pave the way for the use of RMK data to reduce the sample size needed for future clinical trials on chronic stroke patients ( Agrafiotis et al, 2021 ) and to objectively, quantitatively, and rapidly assess impairments in body function ( Moretti et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are in agreement with the studies of Agrafiotis et al ( Agrafiotis et al, 2021 ) and Moretti et al ( Moretti et al, 2021 ), although they analyzed chronic stroke patients. Both studies found a significant correlation between RMK metrics and clinical outcomes (upper limb Fugl-Meyer Assessment ( Agrafiotis et al, 2021 ; Moretti et al, 2021 ), Motor Power ( Agrafiotis et al, 2021 ), NIH stroke scale ( Agrafiotis et al, 2021 ), modified Rankin scale ( Agrafiotis et al, 2021 ), Wolf Motor Function Test ( Moretti et al, 2021 ), Barthel Index ( Moretti et al, 2021 ), and Medical Research Council score ( Moretti et al, 2021 ) demonstrating that traditional stroke assessment scales can be accurately reproduced by robotic measurements. The outcomes of these studies pave the way for the use of RMK data to reduce the sample size needed for future clinical trials on chronic stroke patients ( Agrafiotis et al, 2021 ) and to objectively, quantitatively, and rapidly assess impairments in body function ( Moretti et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Both studies found a significant correlation between RMK metrics and clinical outcomes (upper limb Fugl-Meyer Assessment (Agrafiotis et al, 2021;Moretti et al, 2021), Motor Power (Agrafiotis et al, 2021), NIH stroke scale (Agrafiotis et al, 2021), modified Rankin scale (Agrafiotis et al, 2021), Wolf Motor Function Test (Moretti et al, 2021), Barthel Index (Moretti et al, 2021), and Medical Research Council score (Moretti et al, 2021) demonstrating that traditional stroke assessment scales can be accurately reproduced by robotic measurements. The outcomes of these studies pave the way for the use of RMK data to reduce the sample size needed for future clinical trials on chronic stroke patients (Agrafiotis et al, 2021) and to objectively, quantitatively, and rapidly assess impairments in body function (Moretti et al, 2021). However, most published studies on this topic examined the relationships between technology-based metrics and clinical assessment outcomes measured close in time (e.g., concurrently) (Krebs et al, 2014;Grimm et al, 2021;Olesh et al, 2014;Wang et al, 1109).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations